Large mucinous cystadenoma in pregnancy: a rare case report - Arya, Varsha; Mukherjee, Shubhra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Presence of ovarian tumors in pregnancy is uncommon. In most cases, they are benign, torsion is the most common complication. Management can be conservative or surgical depending on the size, clinical presentation, gestational age, available resources etc. advances in imaging techniques have made the decision making easier. We present a case of primigravida aged 24 years, with 18 weeks’ pregnancy with pain in abdomen. She had a large mass arising from the pelvis. Full work up was done. Imaging was suggestive of mucinous cystadenoma with bilateral hydronephrosis due to mass effect. Laparotomy was done and a 20 kg tumor was removed, histopathology confirmed a huge cystadenoma. Patient was discharged in a stable condition. The management of ovarian tumors in pregnancy can be challenging. Although the safety of antepartum surgical intervention is accepted, abdominal surgery will carry some risk to the pregnant woman and the unborn fetus. Surgery becomes necessary in the presence of rupture, torsion or malignancy.